Karakter Disiplin Siswa SMP Negeri 3 Sungai Penuh - Indah Tria Audina; Junaidi Indrawadi (Journal of Civic Education, 2019)
Abstract The discipline character of students in SMP Penuh 3 Sungai Penuh is not good even though character building has been carried out for students. This can be seen from the fact that there are still students who arrive late, often pull out of school, go out in class during class hours, when the teacher explains the learning students do not listen, and most students are busy with other activities. The type of research used is descriptive qualitative research. The selection of informants is to use purposive sampling, while the informants in this study are: 1 headmaster, 1 vice principal, 8 teacher assemblies, 6 students / scout members, football and volleyball, 1 staff member, 1 Picket teacher, and 1 counseler. The collected data uses observation, interviews and documentation. The results showed that: (1) the disciplinary character development of students in the Sungai Penuh 3 Public Middle School is by way of extracurricular activities that must be followed by students, namely Scouts and sports such as soccer and volleyball and religious activities.(2) Constraints in discipline of students (a) lack of awareness of students, and (b) social environment. (3) Efforts to deal with the constraints of developing disciplinary character of students in Sungai Penuh 3 Public Middle School are: (a) approach by homeroom teacher, (b) cooperation with parents of students, and (c) cooperation with counseler, (d) cooperation with the police. Keywords: Coaching, Discipline Character, Students